2015
DOI: 10.1016/j.febslet.2015.01.030
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐204, down‐regulated in retinoblastoma, regulates proliferation and invasion of human retinoblastoma cells by targeting CyclinD2 and MMP‐9

Abstract: a b s t r a c tAberrant expression of miR-204 had been frequently reported in cancer studies; however, the mechanism of its function in retinoblastoma remained unknown. Here, we reported that miR-204 was frequently downregulated in retinoblastoma tissues and cell lines. Enforced expression of miR-204 inhibited retinoblastoma cells' proliferation and invasion. In vivo study indicated that restoration of miR-204 inhibited tumor growth. CyclinD2 and MMP-9 were identified as potential targets of miR-204. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 30 publications
3
43
0
Order By: Relevance
“…The study has shown that NEAT1 aggravated the lipopolysaccharide (LPS)‐induced rat mesangial cell injury by modulating miR‐204 expression (Y. Chen, Qiu, et al, ). And miR‐204 has been found to be downregulated in RB tissues and cells, and it could suppress the proliferation and invasion of human RB cells (Wu et al, ). Consistent with previous data, we also found miR‐204 expression was decreased in RB tissues and cells (Figure b,c).…”
Section: Resultsmentioning
confidence: 99%
“…The study has shown that NEAT1 aggravated the lipopolysaccharide (LPS)‐induced rat mesangial cell injury by modulating miR‐204 expression (Y. Chen, Qiu, et al, ). And miR‐204 has been found to be downregulated in RB tissues and cells, and it could suppress the proliferation and invasion of human RB cells (Wu et al, ). Consistent with previous data, we also found miR‐204 expression was decreased in RB tissues and cells (Figure b,c).…”
Section: Resultsmentioning
confidence: 99%
“…The miR-204 is a well-characterized microRNA, already shown to be downregulated in many solid tumors [15, 18, 19]. Despite the fact that its mode of action and its effector targets may differ according to the tissue of origin and the stage of the tumor, there is indication that it may represent a general tumor suppressor [15, 1824]. Thus, the data collected here for both GC and CC specimens and the experiments performed in the GTL-16 and HUCCT1 cells are in line with the literature data.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of miR-204 (~2.5-fold) has been observed in human retinoblastoma (RB) tissues and cell lines when compared to normal pediatric retinas [182]. Restoration of miR-204 levels inhibited RB cell migration and invasion capability in vitro and decreased RB tumor growth in vivo.…”
Section: Mir-204 In Glaucoma and Retinoblastomamentioning
confidence: 99%